Análise econométrico-espacial do suicídio no Brasil - Araújo, Rafael de Sousa (2020)
The present study aims to analyze the suicide rates recorded in Brazilian municipalities in the years 2000 and 2010, associating this phenomenon with economic, meteorological and social variables. The analysis starts from the idea defended by Durkheim (2000), who sees suicide as a social problem, and not an individual one. For this, we used data from the Brazilian Institute of Geography and Statistics (IBGE), the United Nations Development Program (UNDP), the Department of Informatics of SUS (DATA-SUS) and the meteorological information base of the University of Delaware. We used a balanced spatial panel with the first difference, as well as other tools of spatial econometrics, considering the minimum distance matrix, which takes into account that each municipality has at least one neighbor. Based on specification tests, we verified that the most appropriate spatial model would be the spatial lag (SAR), showing that the dependent variable (suicide rate) is partially determined by the values of the same variable in neighboring municipalities. Among the main results, it was found that there is a relative overflow effect of suicide among Brazilian municipalities. In addition, it can be seen that the variables aging rate, unemployment rate and average temperature have a positive relationship with the suicide rate; on the other hand, the proportion of people without a defined religion, the proportion of divorces and the volume of rainfall have a negative relationship with the variable of interest.